Women and entrepreneurship for economic growth in Indonesia - Setyaningrum, Retno Purwani; Norisanti, Nor; Fahlevi, Mochammad; Aljuaid, Mohammed; Grabowska, Sandra (Frontiers in Psychology, 2023)
The current government believes that supporting women entrepreneurs is essential for economic growth in Indonesia. This problem is interesting to study because it places women as respondents and examines the effect of (1) Servant Leadership on Indonesia’s Successful Women entrepreneurs, (2) Servant Leadership on self-Efficacy, (3) Self Efficacy on successful women entrepreneurs, (4) Servant leadership to Innovative behavior, (5) innovative behavior to Indonesia’s successful women entrepreneurs, (6) Innovative behavior to Indonesia’s successful women entrepreneurs moderated adoption of e-commerce digitization and (7) Servant leadership to successful women entrepreneurs mediated by self-efficacy. The type of research is a survey that uses female Small and Medium-sized Enterprises (SME) entrepreneurs as respondents in three provinces in Indonesia, namely West Java, Yogyakarta and Jakarta. The sampling technique used is purposive, with a sample size of 234 respondents. The data analysis technique was carried out with AMOS 23. Findings: The results of the research shows that there is a significant positive effect between; (1) Servant Leadership to Indonesia’s Successful Women Entrepreneur, (2) Servant Leadership to self-Efficacy, (3) Self Efficacy to successful women entrepreneurs, (4) Servant leadership to Innovative behavior, (5) Innovative behavior to Indonesia’s successful women entrepreneurs, (6) Innovative behavior to Indonesia’s successful women entrepreneurs moderated by adopted e-commerce digitization and (7) Servant leadership to successful women entrepreneurs mediated by self-efficacy. Purposive sampling has the limitation that it cannot generalize the population in above mentioned three provinces. This is because women entrepreneurs are not limited in their business so each SME has uneven leadership abilities. In addition, the amount of business turnover varies, so several SMEs do not yet have high self-efficacy and low ability to use e-commerce digitalization adoption. SMEs in West Java, DIY and Jakarta still need a lot of training and assistance in management knowledge and leadership methods that are suitable for their business